Out of court settlement of song and music litigations in Indonesia - Tanuatmaja, Hendra (Opción, 2019)
The aim of the study is to investigate out of court settlement of song and music litigations in Indonesia by making a Library Research and adopting a descriptive normative approach. As a result, agreements dealing with the transfer of music copyright should contain a provision on the option of making an amicable out-of-court settlement of disputes or through a dispute settlement mediation institution. In conclusion, it would be better if every agreement dealing with the transfer of music copyright also contains a provision on the option of making an amicable settlement of disputes through a dispute settlement mediation institution.